PERAN GURU PEMBIMBING DALAM PENGEMBANGAN SELF-REGULATED LEARNING - Nur Wangid, Muhammad (Cakrawala Pendidikan, 2006)
something completedskill to self-regulate one's__A ,...today should possess as well aslearners' academic achievement in the classroom_.... ,...... _'... __ learning to take place in the current schoolclassroom such as the learners andas learning tasks, resources, and equipment have toA lotof effort must be made to r'lO'TOrrl.'S"'\learning in a self-regulated way. The roledeveloping that skill in students, especially"""..... '-&"" .................. service, is worth exploring.